Hydrothermal Process Route In The Synthesis Of Zinc Oxide Powder - Ong, Pek Ling (2009)
In this work, zinc oxide powder is synthesized via the hydrothermal method. In the experimental procedure producing the ZnO powder, acetate buffer solution, sodium hydroxide, zinc nitrate hexahydrate solution (0.1 M and 1.0 M) and urea solution (0.2 M and 2.0M) are mixed under stirred condition in a pressure reactor. The molar concentration ratio of zinc nitrate hexahydrate to urea is 1 :2. The reaction time studied was at 3 hours and 5 hours at temperatures of 130°C and 150°C. The precipitates were dried after filtration and then calcination at 400°C. SEM analysis showed different types of morphology observed in the powders produced at varying reaction time and temperature. They were nano flakes-like shape, rod shape and hexagonal rod shape. The average thickness of the nano flakes structure obtained range from 7.49nm to 63.21nm. As for the rod shape particles, the width and length of the rod is 1. 724Jlm and 10.63 Jlm respectively. Overall EDX results, did not show the presence of other elemental peaks. From XRD analysis, the crystallite size of the samples produced range from 197.4A to 662.9A. The percentage of zinc oxide present in the sample from the XRF analysis is around 98.8 %. Results from thermal analysis (TGA/DT A) showed that the zinc oxide powder produced are stable with no significant change in mass. Zinc oxide powder with homogeneous distribution of nano flakes-like structure can be synthesized via hydrothermal process w1der low concentration of chemical precursors and at low reaction temperature and shorter reaction time.